Smart home security access system using field programmable gate arrays - Saleh, Shukur; Mazlan, Sulaiman; Hamzah, Nik Iskandar; Abdul Karim, Ahmad Zahid Zakwan; Zainal, Mohd Shamian; Hamzah, Shipun Anuar; Md Nor, Danial; Mhd Poad, Hazwaj (Institute of Advanced Engineering and Science (IAES), 2018)
Nowadays, the rapid growth of burglary and theft cases over the world has been threatening to the vulnerability of traditional home security systems. Therefore the development home security with intelligent control wherein focus to enhance conventional technique to theadvanced digital security systemand to be more interestinginhome or building owner for preventing intruders in smart home implementation. However, using avariety of type conventional lock doors for security purposes and analog intruder sensor with individual function system is not secure enoughin order to protect the person or company properties. That why the emergence of new technology such as integrated circuit network will apply in Smart Home system for abetter security solution to prevent the houses from theintruder and hazardous fire incident. Therefore, this project is done to design and build a smart system with consist of digital security entry for automatic lock doors and also for activating or deactivate all security sensor in houses which is function for detecting the irregular movement and hot temperature (fire incident) in-house for the domestic residential sector. This product includeswith doors automatic lock system using servo motor and detect irregular movement intruder using PIR motion sensor (HC-SR501) and also measure hot temperature using temperature sensor (LM35). The sensor will transmit theanalog signal to Field Programmable Gate Array (FPGA) the Altera DE2-115 board to be processed and which will then display the status entry after key-in password and activation security system on the LED seven segment displays. The entry login controller will use apush button or switchesavailable on FPGA board that are used to login password for automatic door accessand also able maintained for control home smart security system.